(untitled) (INNOVATIVE ECONOMY, 2021)
Voitko S.V., Yurchyshyn O.Ya. PRINCIPLES OF IMPLEMENTATION OF INNOVATIVE POLICY BASED ON THE DEVELOPMENT OF REGIONAL HUBS 4.0 Purpose. The aim of the article is determining the state of innovative processes in Ukraine and the EU, studying the best practices of the EU on the implementation of the principles of Industry 4.0 for enterprises with the involvement of scientists and support at the state level. Methodology of research. The following methods were used in the study in order to achieve this goal, namely: an abstract and logical method in study the essence of categories and concepts in the field of Industry 4.0; comparative and economic – in the analysis of domestic and world experience in the introduction of innovative products on the basis of Industry 4.0; statistical analysis and generalization – to process an array of statistical and empirical data and formulate the relevant conclusions of the study. Findings. An analysis of the best European practices aimed at the development of Industry 4.0 was carried out. The projects directed on improvement of the state and regional policies directly, their popularization and informing of a society and the projects directed on introduction (transfer) of technologies of Industry 4.0 directly to the enterprises are considered. Some tools of realization of their principles in Ukraine are resulted, their low efficiency is defined. Positive changes in the domestic legislation aimed at improving the process of innovation and digitalization of production are presented: adoption on July 21, 2021 by the Cabinet of Ministers of Resolution No. 750 to promote the implementation of the technological approach “Industry 4.0” in Ukraine. The resolution provides state financial support for the movement of Industry 4.0 in Ukraine through the creation of Centres 4.0, which will search for projects aimed at digitalization of production, further examination of selected projects and their acceleration and technology transfer. Originality. The practical and methodological principles of supporting the Industry 4.0 movement in Ukraine are substantiated, recommendations for ensuring the innovative development of Ukrainian industry are provided. Practical value. It is proposed in accordance with the Resolution to create working structures - 4.0 centres on the basis of infrastructure of higher education institutions, research institutions, etc., which with state support will carry out further examination of innovative projects and their acceleration and register them in parallel (enter the network) as digital hubs (DIH) on the European Smart Specialization Platform. This combination will expand the Centres’ capacity to attract European grants for Ukrainian SMEs to implement technologies related to Industry 4.0 and will enable Ukrainian innovation specialists to gain experience and support from representatives of developed European digital hubs. Key words: innovations; technology transfer; Industry 4.0; digitalization; hub; Centre 4.0.